2022
DOI: 10.1101/2022.05.05.490750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathophysiology of Dyt1 dystonia is mediated by spinal cord dysfunction

Abstract: Dystonia, a neurological disorder defined by abnormal postures and disorganised movements, is thought to be a neural circuit disorder with dysfunction arising within and between multiple brain regions. Given that spinal circuits are the de facto final common pathway for motor control, we sought to determine their contribution to the movement disorder. We confined a dystonia-related mutation to the spinal cord, which led to behavioural and physiological recapitulation of a severe form of inherited, early-onset,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…ALS can spread in a cell-to-cell "domino-like" manner, with a contiguous caudal-to-rostral spinal progression of disease pathology occurring in spinal onset patients; this is also a typical feature observed in mSOD1 mice 38 . Similar progression patterns have been observed in other motor diseases, for example, in a mouse model of dystonia, spinal circuit dysfunction was responsible for a progressive monosynaptic Ia reflex impairment from lower to upper lumbar regions 61 . Through BQA we found that an increase in the probability of release from Ia terminals to lower lumbar motoneurons is likely responsible for enhancement of the proprioceptive Ia afferent drive to motoneurons 43,62,63 .…”
Section: Discussionsupporting
confidence: 75%
“…ALS can spread in a cell-to-cell "domino-like" manner, with a contiguous caudal-to-rostral spinal progression of disease pathology occurring in spinal onset patients; this is also a typical feature observed in mSOD1 mice 38 . Similar progression patterns have been observed in other motor diseases, for example, in a mouse model of dystonia, spinal circuit dysfunction was responsible for a progressive monosynaptic Ia reflex impairment from lower to upper lumbar regions 61 . Through BQA we found that an increase in the probability of release from Ia terminals to lower lumbar motoneurons is likely responsible for enhancement of the proprioceptive Ia afferent drive to motoneurons 43,62,63 .…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, our work here suggests that the effects of KCNQ‐targeting therapies are likely to be restricted to the susceptible subsets of motoneurons in ALS. In addition, hyperexcitability leading to spasticity is a hallmark of other neurological disorders including but not limited to spinal cord injury (Elbasiouny et al., 2010; Gorassini et al., 2004), cerebral palsy (Bar‐On et al., 2015; Condliffe et al., 2016; Reedich et al., 2023; Steele et al., 2020), multiple sclerosis (Beard et al., 2003), stroke (Burke et al., 2013; Mottram et al., 2014; Nielsen et al., 2019; Udby Blicher & Nielsen, 2009) and dystonia (Pocratsky et al., 2023). Although KCNQ channels have not yet been investigated as therapeutic targets in these conditions, they represent promising avenues for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our work here suggests that the effects of KCNQ-targeting therapies are likely to be restricted to the susceptible subsets of motoneurons in ALS. In addition, hyperexcitability leading to spasticity is a hallmark of other neurological disorders including but not limited to spinal cord injury (Elbasiouny et al, 2010;Gorassini et al, 2004), cerebral palsy (Bar-On et al, 2015;Condliffe et al, 2016;Reedich et al, 2023;Steele et al, 2020), multiple sclerosis (Beard et al, 2003), stroke (Burke et al, 2013;Mottram et al, 2014;Nielsen et al, 2019;Udby Blicher & Nielsen, 2009) and dystonia (Pocratsky et al, 2023). Although KCNQ channels have not yet been investigated as therapeutic targets in these conditions, they represent promising avenues for future study.…”
Section: Figure 5 M-currents Control Motoneuron Recruitment On a Popu...mentioning
confidence: 99%